Diversity of Leptospira spp. in Rats and Environment from Urban Areas of Sarawak, Malaysia - Chai, Fung Pui; Lesley Maurice, Bilung; Kasing, Apun; Lela, Su’ut (Hindawi Limited, 2017)
Various prevalence studies on Leptospira in animals and humans, as well as environmental samples, had been conducted worldwide, includingMalaysia. However, limited studies have been documented on the presence of pathogenic, intermediate, and saprophytic Leptospira in selected animals and environments. This study was therefore conducted to detect Leptospira spp. in rats, soil, and water from urban areas of Sarawak using the polymerase chain reaction (PCR) method. A total of 107 rats, 292 soil samples, and 324 water samples were collected fromApril 2014 to February 2015. Pathogenic Leptospira was present in 5.6% (6/107) of rats, 11.6% (34/292) of soil samples, and 1.9% (6/324) of water samples. Intermediate Leptospira was present in 2.7% (8/292) of soil samples and 1.9% (6/324) of water samples. Saprophytic Leptospira was present in 10.3% (11/107) of rats, 1.4% (4/292) of soil samples, and 0.3% (1/324) of water samples. From this study, 76 Leptospira spp. were isolated. Based on DNA sequencing, the dominant Leptospira spp. circulating in urban areas of Sarawak are pathogenic Leptospira noguchii, intermediate Leptospira wolffii serovar Khorat, and saprophytic Leptospirameyeri, respectively.Overall, this study provided important surveillance data on the prevalence of Leptospira spp. from rats and the environment, with dominant local serovars in urban areas of Sarawak.